BOOK PUBLISHING IN PREWAR AND MODERN LITHUANIA: COMPARATIVE ANALYSIS OF THE EXPERIENCE GAINED - MISIŪNAS, REMIGIJUS (Knygotyra, 2014)
This article is based on the paper which was presented in the International Book Science Conference, on Traditional and electronic Publishing in a Small Country: Experience and Perspectives, held in Vilnius in 2013. The aim of this article is to investigate historical parallels in publishing between the two periods of Lithuania’s independence (1918–1940 and after 1990). It can be seen as a brief introduction to the search subject that may prove to be interesting and useful for scientists and those interested in Lithuanian publishing processes.The development of publishing in Lithuania was very similar to the situation in other newly established and re-established countries in Eastern Europe during both independence periods and was mainly influenced by the country’s size, population, economy, culture and educational situation.Despite various obstacles, publishing market demonstrated rapid growth at the beginning of both periods, followed by a slight decline after the introduction of stable national currency in 1922 and in 1993. As the publishers were entering the final stages of their establishment, while trying to adapt to changing market conditions, the repertoire structures appeared and the first leaders emerged. One of the main concerns shared by most publishers during both periods was a relatively small book market which made them pay significant attention to marketing and retail. Soaring print runs 289 indicated constant growth between 1918 and 1940, which was mainly influenced by the expansion of the Lithuanian educational system. Nevertheless, the growth of higher education system during the second period did not have such an impact and the print runs started to shrink since mid-nineties. Additionally, economic down turns of 1930–1932, 1998–2000 and 2008 interrupted the development of publishing as the publishers were focusing their efforts on marketing techniques to increase book sales.The relationship between the government and the publishers has always been important in small countries. Despite publicly declaring the support for book industry, governmental policies appeared to lack clear direction and long-term visions during both periods. As a result, the progress of publishing industry mainly relied on the publishers, who saw their activity as both business and a cultural mission. This article briefly introduces the main parallels between the two periods, but as the research continues the new findings may emerge, therefore it could be seen as a guide for the future search.